Prototype design of readout electronics for Zero Degree Calorimeter in the HIRFL-CSR external-target experiment. (4th August 2021) - Zhu, S.H.; Yang, H.B.; Pei, H.; Zhao, C.X.; Li, X.Q.; Huang, G.M.
Abstract: Located at the center of the end of the CSR External-target Experiment (CEE), the Zero Degree Calorimeter (ZDC) is designed to rebuild the centrality and reaction plane of the nuclear-nuclear collision. To meet the target of ZDC to detect the energy distribution of colliding particles, a high-performance readout system prototype, which implements a Gaussian shaping algorithm, has been designed. The system consists of 4 channels; each channel mainly includes an I-V conversion circuit, a slow forming circuit, a threshold trigger circuit, and a digital signal processing unit based on a field-programmable gate array (FPGA).Performance studies indicate that the noise of each channel is less than 0.8 mV and the nonlinearity is better than 0.6%. Tests with a LED driver source indicate that the Gaussian shaping algorithm can improve the photon energy resolution from 7.481% to 6.196%. Tests with cosmic rays also produced expected results.